Molecular Determination of Virulence Factor Genes of Acinetobacter baumannii Isolates from Clinical Specimens: Life Science-Microbiology - E, Fiji; B, Anandharaj; G Varghese, Jijo (International Journal of Life Science and Pharma Research, 2022)
Acinetobacter baumannii is a gram negative coccobacilli present abundantly in nature, in soil and water. Acinetobacter baumannii is considered as a major cause of nosocomial infections affecting mainly ICU patients and other hospitalised patients. Both intrinsic and acquired antibiotic resistance of A. baumannii account for a significant cause of outbreaks. Significant levels of morbidity and mortality have been reported with outbreaks and common infections include ventilator associated pneumonia and bacteraemia. A.baumannii is also a common cause of bloodstream infections in the intensive care setting. Multiple virulence factors are required for the pathogenesis of infections by Gram negative bacteria including A. baumannii. Possession of specialized virulence genes enables pathogens to infect hosts efficiently. Virulence factors of A. baumannii were less identified compared to other Gram negative bacteria. Hence this study was done to identify the major virulence factor genes from the clinical isolates of multidrug resistant A. baumannii from a tertiary care hospital. A preliminary study was done to determine the prevalence of Acinetobacter infections in the region and then the isolates were subjected to determine the antibiotic sensitivity and to various molecular typing. Various clinical specimens like blood, urine, abscess, vaginal swab were analyzed and 15% of the isolates was confirmed and identified as to be resistant to carbapenems. A molecular typing was done to identify the genes conferring virulence factors. Presence of different genes like Bap, Omp A, EpsA, ptk, AdeG were screened from the isolates. : , , , ,